Synergistic Effects of Cinnamomum verum and Stingless Bee Honey on Isoproterenol-induced Cardiac Hypertrophic Murine Model - Arul Mozhi Padmanabhan; Victor Arokia Doss (World Journal of Traditional Chinese Medicine)
Objective: This study aimed to validate the synergistic effects of Cinnamomum verum (C. verum) barks and stingless bee honey (SBH) against cardiac hypertrophy (CH). Materials and Methods: Isoproterenol (ISO-group II-30 mg/kg)-induced cardiac hypertrophic Wistar rats were used in this study. Hypertrophic rats were treated using the reference drug losartan (LOS Group III: 50 mg/kg) and aqueous extracts of C. verum barks and SBH (ACH Group IV: 250 mg/kg and 250 mg/kg). CH was characterized by electrocardiography, hypertrophic indices, and biochemical estimations such as total glucose, protein, albumin, lipid profiles, cardiac marker enzymes, and histopathological studies. Results: Rats received ISO had increased levels of glucose, protein, cholesterol, triglycerides, very low-density lipoprotein, and low-density lipoprotein, coupled with decreased levels of albumin and high-density lipoprotein. These levels were restored to near normal when treated with ACH extracts of the standard drugs. Contrary to the ISO-induced myocardial damaged hearts, ACH extracts had a profound effect compared to LOS, which was also reflected in histopathological studies. Conclusion: These data explicitly reveal that the ACH have a synergistic cardioprotective (antihypertrophic) effect.